2019
DOI: 10.1007/s40122-019-0122-4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Oxycodone Versus Other Intravenous Strong Opioids for Acute Postoperative Pain Control: A Systematic Review of Randomized Controlled Trials

Abstract: Introduction Optimal pain management is crucial to the postoperative recovery process. We aimed to evaluate the efficacy and safety of intravenous oxycodone with intravenous fentanyl, morphine, sufentanil, pethidine, and hydromorphone for acute postoperative pain. Methods A systematic literature search of PubMed, Cochrane Library, and EMBASE databases was performed for randomized controlled trials published from 2008 through 2017 (inclusive) that evaluated the acute pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…Providing adequate analgesia should be achieved without significant adverse events, and opioids with minimal immunosuppressive characteristics may be reasonable options in such situations where opioid use is indicated. Buprenorphine is highly recommended [43], tramadol and oxycodone can be used as a second option [44], while morphine and fentanyl are not recommended due to side effects and addiction potential [43,45].…”
Section: Opioids and Covid-19mentioning
confidence: 99%
“…Providing adequate analgesia should be achieved without significant adverse events, and opioids with minimal immunosuppressive characteristics may be reasonable options in such situations where opioid use is indicated. Buprenorphine is highly recommended [43], tramadol and oxycodone can be used as a second option [44], while morphine and fentanyl are not recommended due to side effects and addiction potential [43,45].…”
Section: Opioids and Covid-19mentioning
confidence: 99%
“… N.B Current evidence suggests that doses of parenteral morphine and parenteral oxycodone are equivalent ( i.e. 1:1) [ 26 ] …”
Section: Resultsmentioning
confidence: 99%
“…In addition, oxycodone has been reported to be associated with a higher incidence of other side effects than fentanyl, such as dizziness, headache, and sedation. 12,14,25 In particular, Park et al reported significantly higher rates of dizziness even at a potency ratio of 60:1. 8,12 However, according to the results of this study, oxycodone using a potency ratio of 55:1 would not increase the incidence of other side effects compared with fentanyl.…”
Section: Discussionmentioning
confidence: 99%